Non-close-packed three-dimensional quasicrystals - Damasceno, Pablo F.; Glotzer, Sharon C.; Engel, Michael (Journal of Physics: Condensed Matter, 2017)
Quasicrystals are frequently encountered in condensed matter. They are important candidates for equilibrium phases from the atomic scale to the nanoscale. Here, we investigate the computational self-assembly of four quasicrystals in a single model system of identical particles interacting with a tunable isotropic pair potential. We reproduce a known icosahedral quasicrystal and report a decagonal quasicrystal, a dodecagonal quasicrystal, and an octagonal quasicrystal. The quasicrystals have low coordination number or occur in systems with mesoscale density variations. We also report a network gel phase.
EAM Import::2019-03-08